Insect Pest Management on Turfgrass - Eileen A. Buss; Adam G. Dale (EDIS)
Turfgrass is grown in many environments and for different uses, including home lawns, parks, athletic fields, cemeteries, golf courses, sod farms, pastures, and right-of-ways. The intensity of turfgrass insect management largely depends on the turf species, variety, and its intended use. This revised 20-page fact sheet describes how to manage a variety of insect pests including armyworms, bermudagrass mite, cutworms, fire ants, ground pearls, hunting billbug, mole crickets, scales/mealybugs, southern chinch bug, twolined spittlebugs, tropical sod webworm, and white grubs. Written by Eileen A. Buss and Adam G. Dale, and published by the Entomology and Nematology Department, March 2016.